Effect of ethnicity on live birth rates after in vitro fertilisation or intracytoplasmic sperm injection treatment - Jayaprakasan, K.; Pandian, D.; Hopkisson, J.; Campbell, B.K.; Maalouf, W.E. (Wiley, 2014)
Objective To assess the relationship between the ethnicity of women and the clinical success of in vitro fertilisation (IVF) or intracytoplasmic sperm injection (ICSI) treatment. Design Observational cohort study. Setting Nottingham University Research and Treatment Unit in Reproduction (NURTURE), UK. Sample A total of 1517 women, of which 1291 were white Europeans and 226 belonged to an ethnic minority group. All the women were undergoing their first cycle of assisted reproductive technology (ART) between 2006 and 2011. Methods All of the women underwent their first cycle of ART between 2006 and 2011. Main outcome measures Live birth rates following IVF or ICSI treatment. Results Although pre-treatment ovarian reserve variables [mean age, basal follicle stimulating hormone (FSH), and total antral follicle count] were significantly favourable in the ethnic group, the live birth rates were significantly lower in this group (35%) compared with the white European group (43.8%) (relative risk 0.8; 95% CI 0.66–0.97). On logistic regression analysis, ethnicity was an independent predictor of live birth rate (OR 0.688; 95% CI 0.513–0.924). After controlling for the other independent variables (age and FSH), the significant association between ethnicity and live birth rate remained strong (OR 0.591; 95% CI 0.425–0.822) on multivariate logistic regression analysis. Conclusions Live birth rates following IVF or ICSI treatment were significantly lower in the ethnic minority group compared with white European women, which suggests that ethnicity is a major determinant of live birth following IVF treatment.